The Effect of Using Social Media on Student Development in the Learning Process in the Social Science Study Program Branch: A Systematic Review - Lady Agustina; Ali Usman (Studies in Learning and Teaching, 2024)
The research aims to determine the influence of social media on student development in the learning process. The research method adopts Husamah et al. (2022) and Katz & Nandi (2021). The first stage is the critical stage—first, the formulation of research questions. Second, identify studies that are relevant to the research topic—Third, evaluate and select studies that best suit the research objectives. The third stage is the initial screening of documents, selecting documents that have high relevance and selecting using relevant keywords. The research results show that social media has a relatively significant role in learning. Platforms such as Facebook, Twitter, Instagram, and YouTube positively enhance the teaching and learning process. It can further increase students' independence and self-confidence and encourage collaborative work in the classroom environment. However, using social media also has risks, such as reducing productive study time due to excessive interaction. Apart from that, it has a negative impact on interactions between students and teachers. Teachers must pay attention to knowledge construction and social interaction in the learning process. So, teachers can design strategies that utilize the positive potential of social media while actively reducing the negative impacts that may arise. Teachers must take an integrated and thoughtful approach to social media to create a balanced and effective learning environment.